2008
DOI: 10.1017/s0022215108002454
|View full text |Cite
|
Sign up to set email alerts
|

Conductive hearing loss after head trauma: review of ossicular pathology, management and outcomes

Abstract: Cartilage interposition was a very successful method of repairing incudostapedial joint dislocation in this series, at short term follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
1
11
0
2
Order By: Relevance
“…Since most of the attention is primarily focused on stabilizing a patient's overall condition after trauma, a time gap between the accident and diagnosis of an ossicular injury often occurs. The mean delay of 5.5 years in our series is comparable to other studies with average intervals ranging from 5.7 to 8.2 years [4,[6][7][8][9] . The higher incidence of indirect traumas to direct traumas also corresponds to previously published data [5,[7][8][9] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since most of the attention is primarily focused on stabilizing a patient's overall condition after trauma, a time gap between the accident and diagnosis of an ossicular injury often occurs. The mean delay of 5.5 years in our series is comparable to other studies with average intervals ranging from 5.7 to 8.2 years [4,[6][7][8][9] . The higher incidence of indirect traumas to direct traumas also corresponds to previously published data [5,[7][8][9] .…”
Section: Discussionsupporting
confidence: 89%
“…The first cases were treated by restoring the ossicles to their original position or with bone chips, sculpted incus autografts, or allografts [2] . While biocompatible prostheses were initially developed to improve hearing in chronic middle ear disease and otosclerosis, they also proved their usefulness in traumatic disease treatment [2][3][4][5][6][7][8][9] . A recent innovation is the application of hydroxyapatite bone cement, which appears to be a reliable technique to restore the energy transfer in a more physiological way [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence is 30% according to Hollinger et al [1], while a lower incidence (no exact number found) of simultaneous facial nerve paralysis is reported. Incus dislocation is the most common ossicular dislocation, with an incidence up to 63% [1,2,3]. Instances have been reported where the incus was repositioned into either external auditory canal or tympanic antrum, with varying degrees of hearing loss [4,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…5a). Seltener kommt es zu Frakturen, hier sind meist die Stapesschenkel betroffen, teilweise kann es auch zu einer Dislokation desselben in das Vestibulum kommen [2,5]. Mit zeitlicher Latenz können posttraumatische Vernarbungen zu einer Ossikelfixation führen.…”
Section: Verletzungen Der Gehörknöchelchenketteunclassified